Fresh and Post-Thaw Seminal Attributes of Jafarabadi Buffalo Bulls - Parmar, KH; Kavani, FS; Patbandha, TK; Parikh, SS (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
The study was conducted on four Jafarabadi breeding bulls, 5-6 years old to know the fresh and post-thawed seminal characteristicsbased on total of 192 semen ejaculates evaluated and cryopreserved over one year period. The mean values of fresh neat seminalcharacteristics of Jafarabadi bulls, viz., ejaculate volume (ml), colour/density (score), sperm concentration (million/ml), mass activity(score), initial motility (%), live sperm (%), abnormal sperm (%), HOS reactive sperm (%) and acrosomal integrity (%) were 5.19±0.18,2.38±0.10, 1253.36±24.75, 3.73±0.05, 80.31±0.05, 86.20±0.64, 5.00±0.40, 85.75±0.43 and 93.56±0.56, respectively, whereas the meanpost-thawed sperm characteristics, viz., progressive sperm motility, live sperm (%), abnormal sperm (%), HOS reactive sperm (%), acrosomalintegrity (%) and first insemination conception rate (%) observed were 57.60±0.36, 66.34±0.53, 8.85±0.33, 56.97±0.46, 75.26±0.17 and44.63±0.14, respectively. The semen quality of fresh and post-thawed samples observed was within normal limit for use in breedingprogram with satisfactory first insemination conception rate
Keywords: Acrosomal integrity; Conception rate; HOS reactive sperm; Jafarabadi bulls,; Neat semen; Post-thaw seminal traits.